Preparation method of non-noble metal catalytic electrode

Through a simple preparation method, non-precious metal catalytic electrodes with fluffy catalytic layer structure are prepared by using non-precious metal salts, lithium salts and complexing agents, which solves the problems of complex preparation processes and insufficient electrocatalytic activity in the prior art, and achieves efficient, stable and low-cost electrode preparation, which is suitable for commercial applications.

CN119710759APending Publication Date: 2025-03-28HUANENG YIMIN COAL POWER CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411802379.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

In the prior art, the preparation process of non-precious metal catalytic electrodes is complex, and the electrocatalytic activity and stability are insufficient, making it difficult to achieve large-scale, batch preparation and commercial application.

Method used

A method for preparing a non-precious metal catalytic electrode is adopted, including adding a non-precious metal salt to a mixed solution of tackifier, ethanol and water, adding a lithium salt and a complexing agent, adjusting the pH value, forming a slurry and coating on the substrate surface annealing, and then undergoing electrochemical activation.

Benefits of technology

A non-precious metal catalytic electrode with a fluffy catalytic layer structure was prepared, which has good electrocatalytic activity and stability, is suitable for large-scale production, and significantly reduces the cost of electrode materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710759A_ABST
    Figure CN119710759A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a non-noble metal catalytic electrode, and relates to the technical field of clean energy. The preparation method of the non-noble metal catalytic electrode comprises the following steps: S1, adding a non-noble metal salt into a mixed solution of a tackifier, ethanol and water to obtain a first mixed solution; s2, adding a lithium salt into the first mixed solution to obtain a second mixed solution; s3, adding a complexing agent into the second mixed solution, and after the complexing agent is completely dissolved, regulating the pH value of the system to 3-6 by using a pH regulator to obtain a third mixed solution; s4, stirring the third mixed solution until slurry is formed, coating the surface of a substrate with the slurry, and annealing to obtain a to-be-activated electrode; s5, performing electrochemical activation on the to-be-activated electrode to obtain a non-noble metal catalytic electrode; wherein the non-noble metal salt is at least one of transition metal salt and bismuth salt. The preparation method is simple in process, and the prepared non-noble metal catalytic electrode has good catalytic activity and excellent water electrolysis performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of clean energy technology, and in particular to a method for preparing a non-precious metal catalytic electrode. Background Art

[0002] At present, the world continues to promote energy transformation and the degree of electrification continues to advance. Benefiting from the rapid growth of the proportion of clean energy power generation, electrochemical technology has ushered in a new round of development climax and has become a research hotspot in the fields of electrolytic hydrogen production, fuel cells, CO2 conversion and utilization, and electrochemical synthesis of ammonia. Catalytic electrodes are the core components of electrochemical equipment and play a decisive role in the performance of electrochemical reactors. Therefore, they have become a hot issue in related research.

[0003] At present, researchers have developed a variety of methods for preparing catalytic electrodes by means of hydrothermal, gas phase, and electrodeposition. However, although some catalytic electrodes have shown excellent performance at the laboratory level, there are problems such as complex preparation processes and harsh conditions, which make it difficult to achieve large-scale and batch preparation, limiting their application at the commercial level. In addition, some electrode preparation methods are relatively simple and have shown relatively excellent performance in three-electrode systems, but they perform poorly in electrochemical reactors and have poor stability. Therefore, it is urgent to develop simple and efficient catalytic electrode preparation methods with scalability potential to meet commercial application needs. Summary of the invention

[0004] The main purpose of the present invention is to provide a method for preparing a non-precious metal catalytic electrode to solve the problems in the prior art that the preparation process of the non-precious metal catalytic electrode is complicated and the electrocatalytic activity and stability are insufficient in the electrochemical reactor.

[0005] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, a method for preparing a non-precious metal catalytic electrode is provided, and the preparation method comprises the following steps: S1, adding a non-precious metal salt to a mixed solution of a thickener, ethanol and water to obtain a first mixed solution; S2, adding a lithium salt to the first mixed solution to obtain a second mixed solution; S3, adding a complexing agent to the second mixed solution, and after complete dissolution, using a pH regulator to adjust the pH value of the system to 3-6 to obtain a third mixed solution; S4, stirring the third mixed solution until a slurry is formed, coating the slurry on the surface of a substrate, annealing, and obtaining an electrode to be activated; S5, electrochemically activating the electrode to be activated to obtain a non-precious metal catalytic electrode; wherein the non-precious metal salt is at least one of a transition metal salt and a bismuth salt.

[0006] Furthermore, in S1, the transition metal salt includes at least one of copper salt, nickel salt, iron salt, cobalt salt, tin salt and molybdenum salt.

[0007] Furthermore, in S1, the bismuth salt is at least one of bismuth acetate, bismuth nitrate, bismuth chloride, bismuth bromide, and hydrates thereof.

[0008] Furthermore, in S1, the thickener is at least one of ethylene glycol, polyethylene glycol, and diethylene glycol.

[0009] Furthermore, in S2, the lithium salt is at least one of lithium acetate, lithium chloride, lithium bromide, lithium iodide, and hydrates thereof.

[0010] Furthermore, in S3, the complexing agent is citric acid.

[0011] Furthermore, in S3, the pH adjuster is at least one of ammonia water, acetic acid, and nitric acid.

[0012] Furthermore, in S4, the substrate is at least one of nickel felt, titanium felt, nickel foam, stainless steel mesh, and carbon paper.

[0013] Furthermore, in S1, in the first mixed solution, the total concentration of metal ions is 0.1 to 10 mol / L.

[0014] Furthermore, in S1, in the mixed solution of ethylene glycol, ethanol and water, the volume fraction of ethylene glycol is 10% to 20%, and the volume ratio of ethanol to water is 1:3 to 3:1.

[0015] Furthermore, in S2, in the second mixed solution, the ratio of the amount of lithium ions to the total amount of other metal ions is 1:100 to 15:100.

[0016] Furthermore, in S3, the molar ratio of the complexing agent to the metal ions in the second mixed solution is 1:3 to 3:1.

[0017] Furthermore, in S4, the third mixed liquid is stirred at 75-85° C. for 30-90 min to obtain a slurry.

[0018] Furthermore, in S4, the coating amount of the slurry on the substrate is 2 to 5 mg / cm 2 .

[0019] Furthermore, when the non-precious metal catalytic electrode is used as an anode electrode, annealing is performed in an oxygen-containing atmosphere in S4; when the non-precious metal catalytic electrode is used as a cathode electrode, annealing is performed in an inert atmosphere in S4.

[0020] Furthermore, the annealing conditions are: heating to 350-450°C at a rate of 5-20°C / min, keeping warm for 60-120min; then heating to 500-600°C at a rate of 5-20°C / min, keeping warm for 120-240min; finally cooling to room temperature at a rate of 5-20°C / min.

[0021] Further, in S4, the electrochemical activation method is: using the electrode to be activated as the working electrode, a carbon rod, a graphite electrode, a platinum electrode or a titanium electrode as the counter electrode, and a 0.1-1 M XCl solution as the electrolyte, successively using cyclic voltammetry and a step method for activation, washing, and drying to obtain a non-precious metal catalytic electrode; X = K or Na.

[0022] Furthermore, the conditions for activation using cyclic voltammetry are: potential range -0.2 to 2.1 V, scanning speed 5 to 80 mV / s, and number of turns 3 to 8 turns; the conditions for activation using the step method are: setting 0 V, 1.0 V, 1.5 V, and 2.0 V as target potentials, respectively, and the electrolysis time at each potential is 3 to 5 minutes.

[0023] By applying the technical solution of the present invention and designing a preparation method for a non-precious metal catalytic electrode, a non-precious metal catalytic electrode with a fluffy catalytic layer structure can be prepared, which has good electrocatalytic activity and good water electrolysis performance. In addition, the method has a simple process and does not need to be prepared under a harsh environment, and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a test diagram of the water electrolysis performance of the non-precious metal catalytic electrode in Example 1 of the present invention;

[0025] Figure 2 This is a test diagram of the water electrolysis performance of the non-precious metal catalytic electrode in Example 2 of the present invention;

[0026] Figure 3 This is a comparison diagram of the electrochemical active areas of the non-precious metal catalytic electrodes in Example 1 of the present invention and Comparative Example 1;

[0027] Figure 4 The electrolysis performance test diagram of the anode electrode of Example 1 of the present invention, Comparative Example 1 and comparison is shown. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0029] As described in the background of the present invention, the prior art has the problem that the catalytic activity and stability of non-precious metals in electrochemical reactors are insufficient, and the preparation process is complicated. In order to solve the above problems, in a typical embodiment of the present invention, a method for preparing a non-precious metal catalytic electrode is provided, and the preparation method comprises the following steps: S1, adding a non-precious metal salt to a mixed solution of a thickener, ethanol and water to obtain a first mixed solution; S2, adding a lithium salt to the first mixed solution to obtain a second mixed solution; S3, adding a complexing agent to the second mixed solution, and after complete dissolution, using a pH regulator to adjust the pH value of the system to 3-6 to obtain a third mixed solution; S4, stirring the third mixed solution until a slurry is formed, applying the slurry to the surface of the substrate, annealing, and obtaining an electrode to be activated; S5, electrochemically activating the electrode to be activated to obtain a non-precious metal catalytic electrode; wherein the non-precious metal salt is at least one of a transition metal salt and a bismuth salt.

[0030] The present invention uses non-precious metal salts as raw materials for preparing electrocatalytic active substances, avoids the use of precious metals such as platinum and palladium, significantly reduces the cost of electrode materials, and is conducive to large-scale application. By adding non-precious metal salts to a mixed solution of a tackifier, ethanol and water, on the one hand, the uniformity of the first mixed solution can be improved, and on the other hand, it helps to improve the stability of the system after subsequent complexation; on the other hand, it helps to increase the viscosity of the system, promote the formation of a slurry, improve the coating performance, form a thin and uniform catalytic layer on the surface of the substrate, and improve the coverage and consistency of the electrode material. Adding lithium salts can form a crystal structure doped with lithium elements after annealing. Through further electrochemical activation, lithium elements can be removed from the crystal structure, causing certain structural distortions at the microscopic level, while increasing the active sites of the catalytic material and improving the active area, a relatively stable crystal structure is maintained in situ, and the electrocatalytic activity is significantly improved while ensuring the stability of the electrocatalytic active substance.

[0031] In some embodiments, in S1, the transition metal salt includes at least one of copper salt, nickel salt, iron salt, cobalt salt, tin salt and molybdenum salt. Typically, but not limiting, copper salt includes at least one of copper acetate, copper nitrate, copper chloride, copper bromide, and hydrates thereof; nickel salt includes at least one of nickel acetate, nickel nitrate, nickel chloride, nickel bromide, and hydrates thereof; iron salt includes at least one of ferric acetate, ferric nitrate, ferric chloride, ferrous chloride, ferric bromide, and hydrates thereof; cobalt salt includes at least one of cobalt acetate, cobalt nitrate, cobalt bromide, and hydrates thereof; tin salt includes at least one of tin acetate, tin chloride, tin bromide, and hydrates thereof; molybdenum salt includes at least one of sodium molybdate, lithium molybdate, and hydrates thereof; bismuth salt is at least one of bismuth acetate, bismuth nitrate, bismuth chloride, bismuth bromide, and hydrates thereof; thickener is at least one of ethylene glycol, polyethylene glycol, and diethylene glycol.

[0032] The above transition metal salts and bismuth salts have good solubility in a mixture of ethanol and water and can form a clear solution. By adding a thickener, they can initially complex and increase the viscosity of the system, laying the foundation for the subsequent formation of a good slurry.

[0033] In some embodiments, in S1, the non-precious metal salt is a compound of a nickel salt and an iron salt, or a compound of a nickel salt and a molybdenum salt.

[0034] By optimizing the types of non-precious metal salts, the electrocatalytic performance of the non-precious metal catalytic electrode can be further improved, and the water electrolysis performance is good.

[0035] In some embodiments, in S2, the lithium salt is at least one of lithium acetate, lithium chloride, lithium bromide, lithium iodide, and hydrates thereof.

[0036] The above-mentioned lithium salts are widely available, relatively low in cost, and do not introduce additional harmful substances during the preparation process. During the preparation process, lithium ions are easily doped into crystals formed by transition metal salts or bismuth salts, and are easily removed during the subsequent electrochemical activation process, making the electrocatalytic active substances more fluffy and improving the electrocatalytic performance of non-precious metal catalytic electrodes.

[0037] In some embodiments, in S3, the complexing agent is citric acid, and multiple carboxyl groups (-COOH) and hydroxyl groups (-OH) in the citric acid molecule can form stable complexes with non-precious metal ions. These complexes have high solubility in the solution, can effectively prevent the precipitation of metal salts in the solution, improve the dispersibility and uniformity of metal ions, and are conducive to forming a uniform and stable slurry, thereby improving the preparation quality of electrode materials. In addition, during the annealing process, citric acid decomposes, and the released gas can regulate the nucleation and growth of metal oxides or metals, so that the catalyst has a better structure and a larger specific surface area, and enhances the catalytic activity.

[0038] Typically but not limiting, in S3, the pH adjuster is at least one of ammonia, acetic acid, and nitric acid.

[0039] Typically but not limiting, in S4, the substrate is at least one of nickel felt, titanium felt, nickel foam, stainless steel mesh, and carbon paper.

[0040] In some embodiments, in S1, in the first mixed solution, the total concentration of metal ions is 0.1 to 10 mol / L.

[0041] Controlling the total concentration of metal ions within the above range can ensure that the metal salt has good solubility in the mixed solution of ethylene glycol, ethanol and water, forming a uniform first mixed solution, which is beneficial to subsequent coating; in addition, it can also ensure that the loading amount of electrocatalytic active substances is moderate and evenly distributed on the substrate, taking into account both electrocatalytic activity and stability.

[0042] In some embodiments, in S1, in the mixed solution of ethylene glycol, ethanol and water, the volume fraction of ethylene glycol is 10% to 20%, and the volume ratio of ethanol to water is 1:3 to 3:1.

[0043] Controlling the proportion of each component in the mixed solution of ethylene glycol, ethanol and water can make it have good solubility, so that non-precious metal salts can be fully dissolved. On the other hand, it can effectively increase the viscosity of the first mixed solution to form a slurry with suitable viscosity to facilitate coating.

[0044] In some embodiments, in S2, in the second mixed solution, the ratio of the amount of lithium ions to the total amount of other metal ions is 1:100 to 15:100.

[0045] Controlling the content of lithium ions is, on the one hand, to increase the specific surface area of ​​the electrocatalytically active material and improve the catalytic activity of the non-precious metal catalytic electrode; on the other hand, it is to make the electrocatalytically active material have good stability and a long service life.

[0046] In some embodiments, when preparing the first mixed solution and the second mixed solution, stirring is continued, and the stirring method is ultrasonic or mechanical stirring. Stirring can improve the preparation efficiency and make the components in the first mixed solution and the second mixed solution more evenly distributed.

[0047] In some embodiments, in S4, the third mixed solution is stirred at 75-85° C. for 30-90 min to obtain a slurry.

[0048] Stirring at 75-85°C can increase the rate of the complexation reaction, and within this temperature range, the viscosity and fluidity of the solution are moderate, which is conducive to the formation of a stable and uniformly distributed complex. In addition, the viscosity of the slurry formed under the above conditions is moderate, and it is easy to form a uniform catalytic layer of suitable thickness.

[0049] In some embodiments, in S4, the coating amount of the slurry on the substrate is 2 to 5 mg / cm 2 .

[0050] The amount of slurry applied should be controlled at 2-5 mg / cm 2 It can optimize the thickness and uniformity of the catalytic layer, improve the conductivity, thermal stability and mechanical strength of the electrode, and also achieve a good balance in terms of economy and reaction kinetics.

[0051] Typically but not limiting, the coating method in S4 includes spin coating, blade coating, brush coating, etc.

[0052] In some embodiments, when the non-precious metal catalytic electrode is used as an anode electrode, in S4, annealing is performed in an oxygen-containing atmosphere; when the non-precious metal catalytic electrode is used as a cathode electrode, in S4, annealing is performed in an inert atmosphere. Typically but not limiting, the oxygen-containing atmosphere is a mixture of oxygen and an inert gas, wherein the volume proportion of oxygen is 3% to 10%; the inert gas includes at least one of nitrogen, argon, and helium.

[0053] When used as an anode electrode, the electrocatalytically active substance is an oxidizing substance and needs to be calcined in an oxygen-containing atmosphere; when used as a cathode electrode, the electrocatalytically active substance is a reducing substance and calcination in an inert atmosphere can avoid the introduction of impurities.

[0054] In some embodiments, the annealing conditions are: heating to 350-450°C at a rate of 5-20°C / min, and keeping warm for 60-120 min; then heating to 500-600°C at a rate of 5-20°C / min, and keeping warm for 120-240 min; finally cooling to room temperature at a rate of 5-20°C / min.

[0055] Controlling the annealing conditions can reduce the internal stress in the electrocatalytically active material, reduce the number of crystal defects, and improve the mechanical strength and electrocatalytic activity of the electrocatalytically active material.

[0056] In some embodiments, in S4, the electrochemical activation method is: using the electrode to be activated as the working electrode, using a carbon rod, a graphite electrode, a platinum electrode (platinum mesh, platinum wire, platinum wire, etc.) or a titanium electrode as the counter electrode, using a 0.1-1M XCl solution as the electrolyte, successively using cyclic voltammetry and step method for activation, washing, drying, to obtain a non-precious metal catalytic electrode; X = K or Na. Among them, the conditions for activation by cyclic voltammetry are: potential range -0.2-2.1V, scanning speed 5-80mV / s, 3-8 turns; the conditions for activation by step method are: setting 0V, 1.0V, 1.5V, 2.0V as the target potential (setting the electrode fluctuation range ±0.1V), and the electrolysis time at each potential is 3-5 minutes.

[0057] The above activation can release lithium ions from the electrode to be activated, making the structure of the electrocatalytic active material more fluffy, with a higher specific surface area and electrochemical active area, which is beneficial to improving the electrocatalytic activity of the non-precious metal catalytic electrode.

[0058] In some embodiments, when cyclic voltammetry is used for activation, the scan rate is 5 to 30 mV / s.

[0059] Activation under the above conditions can, on the one hand, control the reaction depth and avoid excessive oxidation or reduction that leads to a decrease in catalyst performance; on the other hand, it can remove pollutants and passivation layers on the electrode surface, improve the structure of the catalyst surface, expose more active sites, and improve catalytic activity and stability.

[0060] In some embodiments, washing and drying are performed after electrochemical activation; specifically, deionized water, ultrapure water or distilled water is used for washing, and then it is immersed in ethanol or acetone, and then placed in a vacuum drying oven for drying, the drying temperature is 60 to 80° C., and the drying time is 6 to 18 hours.

[0061] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0062] Example 1

[0063] An embodiment of a method for preparing a non-precious metal catalytic electrode of the present invention comprises:

[0064] S1, adding 0.1 mol of nickel acetate tetrahydrate and 0.1 mol of ferric nitrate nonahydrate to 50 mL of a mixed solution of ethylene glycol, ethanol and water (the volume fraction of ethylene glycol is 10%, and the volume ratio of ethanol to water is 3:1) under stirring, and after they are completely dissolved, a first mixed solution is obtained;

[0065] S2, adding 0.0294 mol of lithium acetate dihydrate to the first mixed solution under stirring to obtain a second mixed solution;

[0066] S3, adding 0.3 mol of citric acid to the second mixed solution, and after it is completely dissolved, adjusting the pH value of the system to 4.5 with 1 mol / L acetic acid solution to obtain a third mixed solution;

[0067] S4, stirring the third mixed solution at 80° C. for 45 min to form a slurry, and spin-coating the slurry on a nickel felt with a porosity of 80% at a coating amount of 3 mg / cm 2 ; Place it in a mixture of oxygen and argon with an oxygen volume ratio of 5%, heat it to 400°C at a rate of 10°C / min, keep it warm for 90 minutes, then heat it to 550°C at a rate of 5°C / min, keep it warm for 180 minutes; finally cool it to room temperature at a rate of 10°C / min to obtain an electrode to be activated;

[0068] S5, electrochemically activate the electrode to be activated, using the electrode to be activated as the working electrode, a graphite electrode as the counter electrode, and a 1M KCl solution as the electrolyte, firstly using cyclic voltammetry to scan 3 times in the range of -0.2 to 2.1 V, with a scanning speed of 10 mV / s; then using a step method for deep activation, setting four potentials of 0 V, 1.0 V, 1.5 V and 2.0 V, respectively, and electrolyzing for 4 minutes to complete the activation; rinsing with ultrapure water, immersing the electrode in nitrogen-saturated acetone, and then drying it in a vacuum oven at 80°C for 12 hours to obtain a non-precious metal catalytic electrode.

[0069] The non-precious metal catalytic electrode obtained in this example was used as the anode electrode, and Pt / C with a Pt mass fraction of 40 wt% was used as the cathode catalyst, which was sprayed on the surface of the PiperION (Versogen) anion exchange membrane. The Pt / C loading was 1 mg / cm 2 , assembled with the anode electrode as a membrane electrode, using 1M KOH solution as the electrolyte, and conducting a water electrolysis hydrogen production test in an electrolytic cell. A PiperION membrane sprayed with Pt / C and IrO2 (the mass ratio of the two is 2:3) was used as a comparative anode electrode, with a Pt / C loading of 1 mg / cm 2 , IrO2 loading is 1.5mg / cm 2 , tested under the same conditions, the test results are as follows Figure 1 As shown. By comparison, at 1A / cm 2 Under the conditions, the applied potential was reduced by 100 mV compared with the control anode electrode, proving that it has excellent water electrolysis performance.

[0070] Example 2

[0071] An embodiment of a method for preparing a non-precious metal catalytic electrode of the present invention comprises:

[0072] S1, adding 0.1 mol of nickel acetate tetrahydrate and 0.1 mol of sodium molybdate dihydrate to 50 mL of a mixed solution of ethylene glycol, ethanol and water (the volume fraction of ethylene glycol is 8%, and the volume ratio of ethanol to water is 1:3) under stirring, and after they are completely dissolved, a first mixed solution is obtained;

[0073] S2, adding 0.0294 mol of lithium acetate dihydrate to the first mixed solution under stirring to obtain a second mixed solution;

[0074] S3, adding 0.3 mol of citric acid to the second mixed solution, and after it is completely dissolved, adjusting the pH value of the system to 4.5 with 1 mol / L acetic acid solution to obtain a third mixed solution;

[0075] S4, stirring the third mixed solution at 80°C for 52 minutes to form a slurry, and spin-coating the slurry on carbon paper with a coating amount of 3 mg / cm 2 ; Place it in argon gas, heat it to 400°C at a rate of 5°C / min, keep it warm for 120min, then heat it to 560°C at a rate of 8°C / min, keep it warm for 200min; finally cool it to room temperature at a rate of 5°C / min to obtain an electrode to be activated;

[0076] S5, electrochemically activate the electrode to be activated, using the electrode to be activated as the working electrode, a titanium electrode as the counter electrode, and a 1M KCl solution as the electrolyte. First, cyclic voltammetry is used to scan 5 times in the range of -0.2 to 2.1 V, with a scanning speed of 10 mV / s; then a step method is used for deep activation, and four potentials of 0 V, 1.0 V, 1.5 V and 2.0 V are set respectively, and electrolysis is performed for 4 minutes respectively to complete the activation; rinse with ultrapure water, immerse the electrode in nitrogen-saturated acetone, and then dry it in a vacuum oven at 80°C for 12 hours to obtain a non-precious metal catalytic electrode.

[0077] The non-precious metal catalytic electrode obtained in this example was used as the cathode electrode, and IrO2 was selected as the anode catalyst and sprayed on the surface of PiperION (Versogen) anion exchange membrane. The IrO2 loading was 1.5 mg / cm 2 , assembled with the cathode electrode as a membrane electrode, using 1M KOH solution as the electrolyte, and conducting a water electrolysis hydrogen production test in an electrolytic cell. A PiperION membrane sprayed with Pt / C and IrO2 (the mass ratio of the two is 2:3) was used as a comparative cathode electrode, with a Pt / C loading of 1 mg / cm 2 , IrO2 loading is 1.5mg / cm 2 , tested under the same conditions, the test results are as follows Figure 2 As shown. By comparison, at 1A / cm 2 Under the conditions, the applied potential was reduced by 70 mV compared with the control cathode electrode, proving that it has excellent water electrolysis performance.

[0078] Comparative Example 1

[0079] A method for preparing a non-precious metal catalytic electrode, the method comprising the following steps:

[0080] S1, adding 0.1 mol of nickel acetate tetrahydrate and 0.1 mol of ferric nitrate nonahydrate to 50 mL of a mixed solution of ethylene glycol, ethanol and water (the volume fraction of ethylene glycol is 10%, and the volume ratio of ethanol to water is 3:1) under stirring, and after they are completely dissolved, a first mixed solution is obtained;

[0081] S2, adding 0.3 mol of citric acid to the first mixed solution, and after it is completely dissolved, adjusting the pH value of the system to 4.5 with 1 mol / L acetic acid solution to obtain a second mixed solution;

[0082] S3, stirring the second mixed solution at 80°C for 45 minutes to form a slurry, and spin-coating the slurry on a nickel felt with a porosity of 80% at a coating amount of 3 mg / cm 2 ; Place it in a mixture of oxygen and argon with an oxygen volume ratio of 5%, heat it to 400°C at a rate of 10°C / min, keep it warm for 90 minutes, then heat it to 550°C at a rate of 5°C / min, keep it warm for 180 minutes; finally cool it to room temperature at a rate of 10°C / min to obtain an electrode to be activated;

[0083] S4, electrochemically activate the electrode to be activated, using the electrode to be activated as the working electrode, a graphite electrode as the counter electrode, and a 1M KCl solution as the electrolyte. First, cyclic voltammetry is used to scan 3 times in the range of -0.2 to 2.1 V, with a scanning speed of 10 mV / s; then a step method is used for deep activation, and four potentials of 0 V, 1.0 V, 1.5 V and 2.0 V are set respectively, and electrolysis is performed for 4 minutes respectively to complete the activation; rinse with ultrapure water, immerse the electrode in nitrogen-saturated acetone, and then dry it in a vacuum oven at 80°C for 12 hours to obtain a non-precious metal catalytic electrode.

[0084] The non-precious metal catalytic electrode was used as the anode electrode, and Pt / C with a Pt mass fraction of 40 wt% was used as the cathode catalyst, which was sprayed on the surface of PiperION (Versogen) anion exchange membrane. The Pt / C loading was 1 mg / cm 2 , assembled with the anode electrode as a membrane electrode, using 1M KOH solution as the electrolyte, and conducting a water electrolysis hydrogen production test in an electrolytic cell. A PiperION membrane sprayed with Pt / C and IrO2 (the mass ratio of the two is 2:3) was used as a comparative anode electrode, with a Pt / C loading of 1 mg / cm 2 , IrO2 loading is 1.5mg / cm 2 , tested under the same conditions, the test results are as follows Figure 1 As shown. By comparison, at 1A / cm 2 Under the conditions, compared with the control anode electrode, the applied potential was reduced by 30 mV, and its water electrolysis performance was worse than that of the non-precious metal catalytic electrode in Example 1 of the present invention.

[0085] The electrochemical active areas of Example 1 and Comparative Example 1 were tested and compared using the capacitance method. Figure 3In the figure, the slope of the graph is proportional to the electrochemically active surface area of ​​the test sample, indicating that the non-precious metal catalytic electrode obtained in Example 1 has a larger active surface area, proving that the addition of lithium salt plays an important role in improving the electrochemically active surface area.

[0086] Comparative Example 2

[0087] A method for preparing a non-noble metal catalytic electrode, the preparation method comprising:

[0088] S1, adding 0.1 mol of nickel acetate tetrahydrate and 0.1 mol of sodium molybdate dihydrate to 50 mL of a mixed solution of ethylene glycol, ethanol and water (the volume fraction of ethylene glycol is 8%, and the volume ratio of ethanol to water is 1:3) under stirring, and after they are completely dissolved, a first mixed solution is obtained;

[0089] S2, adding 0.3 mol of citric acid to the second mixed solution, and after it is completely dissolved, adjusting the pH value of the system to 4.5 with 1 mol / L acetic acid solution to obtain a third mixed solution;

[0090] S3, stirring the third mixed solution at 80°C for 52 minutes to form a slurry, and spin-coating the slurry on carbon paper with a coating amount of 3 mg / cm 2 ; Place it in argon gas, heat it to 400°C at a rate of 5°C / min, keep it warm for 120min, then heat it to 560°C at a rate of 8°C / min, keep it warm for 200min; finally cool it to room temperature at a rate of 5°C / min to obtain an electrode to be activated;

[0091] S4, electrochemically activate the electrode to be activated, using the electrode to be activated as the working electrode, a titanium electrode as the counter electrode, and a 1M KCl solution as the electrolyte. First, cyclic voltammetry is used to scan 5 times in the range of -0.2 to 2.1 V, with a scanning speed of 10 mV / s; then a step method is used for deep activation, and four potentials of 0 V, 1.0 V, 1.5 V and 2.0 V are set respectively, and electrolysis is performed for 4 minutes respectively to complete the activation; rinse with ultrapure water, immerse the electrode in nitrogen-saturated acetone, and then dry it in a vacuum oven at 80°C for 12 hours to obtain a non-precious metal catalytic electrode.

[0092] The non-precious metal catalytic electrode was used as the cathode electrode, and IrO2 was selected as the anode catalyst and sprayed on the surface of PiperION (Versogen) anion exchange membrane. The IrO2 loading was 1.5 mg / cm 2 , assembled with the cathode electrode as a membrane electrode, using 1M KOH solution as the electrolyte, and conducting a water electrolysis hydrogen production test in an electrolytic cell. A PiperION membrane sprayed with Pt / C and IrO2 (the mass ratio of the two is 2:3) was used as a comparative cathode electrode, with a Pt / C loading of 1 mg / cm2 , IrO2 loading is 1.5mg / cm 2 , tested under the same conditions, the test results are as follows Figure 2 As shown. By comparison, at 1A / cm 2 Under the conditions, compared with the comparative cathode electrode, the applied potential was reduced by 20 mV, and its water electrolysis performance was worse than that of the non-precious metal catalytic electrode in Example 2 of the present invention.

[0093] At 1A / cm 2 The membrane electrode composed of Example 1, Comparative Example 1 and the comparative anode electrode was tested for water electrolysis performance at a current density of Figure 4 As shown in the figure, it can be seen that after 100 hours of electrolysis, the potential decay rate of Example 1 is the lowest, only 298μV / h, and the decay rate of Comparative Example 1 is about twice that of Example 1. This result shows that the non-precious metal catalytic electrode prepared by the method of the present invention has both good catalytic activity and good stability, and is suitable for large-scale production.

[0094] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a non-precious metal catalytic electrode, characterized in that: The steps include: S1, adding a non-precious metal salt to a mixed solution of a thickener, ethanol and water to obtain a first mixed solution; S2, adding lithium salt to the first mixed solution to obtain a second mixed solution; S3, adding a complexing agent to the second mixed solution, and after the complexing agent is completely dissolved, using a pH adjuster to adjust the pH value of the system to 3-6 to obtain a third mixed solution; S4, stirring the third mixed liquid until a slurry is formed, coating the slurry on the surface of the substrate, and annealing to obtain an electrode to be activated; S5, electrochemically activating the electrode to be activated to obtain the non-precious metal catalytic electrode; Wherein, the non-precious metal salt is at least one of a transition metal salt and a bismuth salt.

2. The method for preparing a non-precious metal catalytic electrode according to claim 1, characterized in that: In S1, the transition metal salt includes at least one of copper salt, nickel salt, iron salt, cobalt salt, tin salt and molybdenum salt; and / or, the thickener is at least one of ethylene glycol, polyethylene glycol and diethylene glycol; and / or, in S2, the lithium salt is at least one of lithium acetate, lithium chloride, lithium bromide, lithium iodide and hydrates thereof; and / or, in S3, the complexing agent is citric acid; and / or, the pH adjusting agent is at least one of ammonia water, acetic acid and nitric acid; and / or, in S4, the substrate is at least one of nickel felt, titanium felt, nickel foam, stainless steel mesh and carbon paper.

3. The method for preparing a non-precious metal catalytic electrode according to claim 1, characterized in that: In S1, in the first mixed solution, the total concentration of metal ions is 0.1-10 mol / L; and / or, in the mixed solution of ethylene glycol, ethanol and water, the volume fraction of ethylene glycol is 10%-20%, and the volume ratio of ethanol to water is 1:3-3:

1.

4. The method for preparing a non-precious metal catalytic electrode according to any one of claims 1 to 3, characterized in that: In S2, in the second mixed solution, the ratio of the amount of lithium ions to the total amount of other metal ions is 1:100 to 15:

100.

5. The method for preparing a non-precious metal catalytic electrode according to any one of claims 1 to 3, characterized in that: In S3, the molar ratio of the complexing agent to the metal ions in the second mixed solution is 1:3 to 3:

1.

6. The method for preparing a non-precious metal catalytic electrode according to any one of claims 1 to 3, characterized in that: In S4, the third mixed solution is stirred at 75-85° C. for 30-90 min to obtain a slurry; and / or the coating amount of the slurry on the substrate is 2-5 mg / cm 2 .

7. The method for preparing a non-precious metal catalytic electrode according to any one of claims 1 to 3, characterized in that: When the non-precious metal catalytic electrode is used as an anode electrode, annealing is performed in an oxygen-containing atmosphere in S4; when the non-precious metal catalytic electrode is used as a cathode electrode, annealing is performed in an inert atmosphere in S4.

8. The method for preparing a non-precious metal catalytic electrode according to claim 7, characterized in that: The annealing conditions are: heating to 350-450°C at a rate of 5-20°C / min, keeping the temperature for 60-120min; then heating to 500-600°C at a rate of 5-20°C / min, keeping the temperature for 120-240min; and finally cooling to room temperature at a rate of 5-20°C / min.

9. The method for preparing a non-precious metal catalytic electrode according to any one of claims 1 to 3, characterized in that: In S4, the electrochemical activation method is: using the electrode to be activated as the working electrode, a carbon rod, a graphite electrode, a platinum electrode or a titanium electrode as the counter electrode, and a 0.1-1M XCl solution as the electrolyte, successively using cyclic voltammetry and a step method for activation, washing and drying to obtain the non-precious metal catalytic electrode; X = K or Na.

10. The method for preparing a non-precious metal catalytic electrode according to claim 9, characterized in that: The conditions for activation by the cyclic voltammetry method are: potential range -0.2 to 2.1 V, scanning speed 5 to 80 mV / s, and number of turns 3 to 8 turns; the conditions for activation by the step method are: setting 0 V, 1.0 V, 1.5 V, and 2.0 V as target potentials, respectively, and the electrolysis time at each potential is 3 to 5 minutes.